Interceding role of institutional extension services on the livelihood impacts of drought tolerant maize technology adoption in Zimbabwe - Makate, C.; Makate, Marshall (Elsevier BV, 2018)
© 2018 Elsevier Ltd The study investigates whether access to agricultural extension services enhances the well-known positive impact of adopting Drought Tolerant Maize (DTM) technology on livelihood outcomes; maize yield, output per capita, consumption and sales using a representative dataset of smallholder farming households from Zimbabwe. The empirical analysis adopts an instrumental variable regression model that incorporates an endogenous interaction term to capture the intermediary role of institutional extension services. Results reveal that access to agricultural extension services enhances the relationship between DTM adoption and maize yield, output per capita, and consumption but appears to weaken the association between DTM adoption and the amount of maize set aside for sale. In exploring the potential reasons why access to institutional extension services might enhance the DTM adoption-livelihood outcomes relationship, the results suggest mechanisms related to the use of basal fertilizers, use of organic manure, access to agricultural credit, use of certified DTM seed, access to general production and marketing information, weeding frequency and disease control which are more likely to be influenced by access to agricultural extension services. The findings suggest that policies targeted at improving DTM adoption as a climate-smart agricultural technology to improve resilience of smallholder maize farming households to climate variability and change must be complemented by revitalized agriculture extension services. Revitalization of extension services may come through capacity building of extension institutions, and their personnel, improving agricultural extension infrastructure, mobility of extension personnel, and increased financing to such institutions.